Problem-Based Learning With Mind Mapping in Respiration System to Improve Creativity of High School Students - Arbain, Rukmin; Abdullah, Faradila Abdullah; Hasan, Nurul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to identify the development of creative thinking skills among students with problem-based learning models with mind mapping. This study is a quasi-experiment using a non-equivalent control-group design. The population of this study was in eleventh grade of the mathematics and natural science program of SMAN 1 CISARUA year 2018/2019 with respiration system as material. Used two classes as a sample which implemented learning models in the respiratory system. XI MIPA 3 was an experimental group implementing problem-based learning with mind mapping and XI MIPA1 was a control group. The result shows there is an increase in student's creativity to 56.80%. Therefore problem-based learning with mind mapping is increasing students' creativity.